(3EOGQI GdYedjGJ hHMhK GdYedjGJs - (3aGgjO(B, (3dWajs; (3cGQ HjLdQ(B, s ((3GdQjGV(B:s (3OGQ GdeQjN ddfTQ,s, 2007)
(3jVe GdJTjjO hYQV YGe, HOA fXe GdHQGeL, JMdjd GdbQGQ HGdLOGhd, JMdjd GdbQGQ HGdCTLGQ, JfHD GdSdGSd GdRefjI, GdGfMOGQ GdeJYOO, JMdjd GdehbY, JMdjd GdJNWjW GdOGNdj, ehGRfI GdNW, GdHQeLI GdNWjI, GdHQeLI ZjQ GdcSQjI GdYGeI, WQjbI GdJNUjU, JNWjW GdGfJGL, JhcjO GdLhOI, JMdjd GdeNRhf(B1(3, JMdjd GdeNRhf(B2(3, JNWjW GdeJWdHGJ ef GdehGO, LOhdI hQTI GdYed, GOGQI GdeTQhY, JMdjd GdUaha, JMdjd eGQcha, feGPL JOab GdTHcGJ(B.s
Keywords: (3EJNGP GdbQGQGJ(B- (3GdEOGQIs; (3GdEOGQIs; (3HMhK GdYedjGJs